The rule of law and the measure of property - Waldron, Jeremy (The Hamlyn lectures)
"When property rights and environmental legislation clash, what side should the Rule of Law weigh in on? It is from this point that Jeremy Waldron explores the Rule of Law both from an historical perspective - considering the property theory of John Locke - and from the perspective of modern legal controversies. This critical and direct account of the relation between the Rule of Law and the protection of private property criticizes the view - associated with the 'World Bank model' of investor expectations - that a society which fails to protect property rights against legislative restriction is failing to support the Rule of Law. In this book, developed from the 2011 Hamlyn Lectures, Waldron rejects the idea that the Rule of Law privileges property rights over other forms of law and argues instead that the Rule of Law should endorse and applaud the use of legislation to achieve valid social objectives"--